Heat extraction from salinity-gradient solar ponds using heat pipe heat exchangers - Sura Tundee (2018)
This paper presents the results of experimental and theoretical analysis on the heat extraction process from solar pond by using the heat pipe heat exchanger. In order to conduct research work, a small scale experimental solar pond with an area of 7.0m2and a depth of 1.5m was built at Khon Kaen in North-Eastern Thailand (16°27'N102°E). Heat was successfully extracted from the lower convective zone (LCZ) of the solar pond by using a heat pipe heat exchanger made from 60 copper tubes with 21mm inside diameter and 22mm outside diameter. The length of the evaporator and condenser section was 800mm and 200mm respectively. R134a was used as the heat transfer fluid in the experiment. The theoretical model was formulated for the solar pond heat extraction on the basis of the energy conservation equations and by using the solar radiation data for the above location. Numerical methods were used to solve the modeling equations. In the analysis, the performance of heat exchanger is investigated by varying the velocity of inlet air used to extract heat from the condenser end of the heat pipe heat exchanger (HPHE). Air velocity was found to have a significant influence on the effectiveness of heat pipe heat exchanger. In the present investigation, there was an increase in effectiveness by 43% as the air velocity was decreased from 5m/s to 1m/s. The results obtained from the theoretical model showed good agreement with the experimental data. © 2010 Elsevier Ltd.